Management of diversity in Peruvian companies: The cases of IBM, Atento and Scotiabank - Gastelú Ledesma, Isabel; Martinez-Hague, Paloma (360: Revista de Ciencias de la Gestión, 2021)
The management of diversity is important today, as proven by the varied research available on this topic. However, when we wanted to understand the management of LGBT diversity, we found little research worldwide, let alone in Latin America. We found a measurement model in the region developed by the Ethos Institute of Brazil which allowed us to understand the current situation of LGBT diversity management in three companies in Peru. Since Peru and Brazil are both Latin American countries, one could think that the model is international and transversal to both realities. However, our research proposed an adaptation of the model to simplify it because elements found in Brazil were not yet present in Peruvian companies. This qualitative investigation applies the adapted and contextualized instrument to three large companies in Peru and presents a rather unique and interesting view of LGBT diversity management.